2007
DOI: 10.1097/gim.0b013e318156e8c1
|View full text |Cite
|
Sign up to set email alerts
|

Development of genomic reference materials for Huntington disease genetic testing

Abstract: These DNA materials, which are available from Coriell Cell Repositories, will facilitate accurate and reliable Huntington genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
4
22
0
Order By: Relevance
“…The results were completely concordant with the verified allele sizes of all samples [3,4] (fig. 1).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The results were completely concordant with the verified allele sizes of all samples [3,4] (fig. 1).…”
Section: Resultssupporting
confidence: 75%
“…RFU = Relative fluorescence units; NL = normal allele; IA = intermediate allele; EX = expanded allele; NA = not applicable. Sample IDs and their verified sizes [3] are shown in the right top corner. Sizes obtained from this study are indicated by arrows.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 90 participants and 270 challenges, there were three "serious genotyping errors" (1.1%, 95% CI: 0.2-3.2%). Given the general availability of specific HD reference material for sizing, 14 it is unclear why these international laboratories participating in the CAP/ACMG survey are not performing to a higher standard. Information was not collected to determine whether these international participants were licensed by CLIA, and certified by CAP, New York State Department of Health, or an equivalent governmental/professional organization.…”
Section: Discussionmentioning
confidence: 99%
“…These include materials for various inherited genetic disorders, such as cystic fibrosis, 7 Huntington disease, 8 Fragile X, 9 and genetic conditions with relatively high prevalence in the Ashkenazi Jewish population 10 (for example, Bloom syndrome, Canavan disease, Fanconi anemia, Tay Sachs disease, familial dysautonomia, Gaucher disease, glycogen storage disease type 1a, Mucolipidosis IV, and Niemann-Pick disease). The program is currently developing new cell lines and conducting RM (on the lower level of the hierarchy) commutability and genotype characterization studies for Duchenne muscular dystrophy, pharmacogenetic loci and disorders included in the American College of Medical Genetics newborn screening panel.…”
Section: Discussionmentioning
confidence: 99%
“…Though sponsored by the CDC, much of the work performed by the GeT-RM, including RM priority decisions, specimen collection, material development, and molecular genetic characterization, occurs through voluntary collaborations with various clinical genetic laboratories. To date, the GeT-RM program has coordinated the development and/or commutability/genotype characterization of RMs for cystic fibrosis, 7 Huntington disease, 8 fragile X syndrome, 9 and several genetic conditions with relatively high prevalence in the Ashkenazi Jewish population 10 ; and has also provided information for several pharmacogenetic markers, including members of the CYP450 gene family, VKORC1, and UGT1A1.…”
mentioning
confidence: 99%